Bionomic Analysis of Skipjack Fish Landed at Ternate Archipelago Fishing Port - Gay, Rohana; Rumagia, Faizal; Ahmad, Adityawan (Agrikan Jurnal Agribisnis Perikanan, 2024)
Skipjack tuna (Katsuwanus pelamis) is one of the important economically fish that landed in Ternate Archipelago Fishing Port (PPN Ternate). The management production of the skipjack tuna that landed in this fishing port become important to manage the fishing activity for this species. This research aims to examine the condition of management and utilization of skipjack tuna that landed in Ternate Archipelago Fishing Port (PPN Ternate) using the bionomic approach. The data were analysis using the bionomic formula within Clarke Yoshimoto Pooley (CYP) model for the biological parameter (r, K, q). The result showed that, the Skipjack tuna fisheries that landed in PPN Ternate has an MSY value of 1.874.382,57 kg per year with an effort of 132 trips per year, while the MEY value was 1.872.946,43 kg per year with an effort of 128 trips per year. The Total Revenue (TR) that earn in the MSY position was IDR. 30.927.312.375 within the Total Cost (TC) was IDR. 1.712.144.935.